Patients With Becker Muscular Dystrophy Have Severe Paraspinal Muscle Involvement - Sheikh, Aisha M.; Rudolf, Karen; de Stricker Borch, Josefine; Khawajazada, Tahmina; Witting, Nanna; Vissing, John (Frontiers in Neurology, 2021)
Introduction: Paraspinal muscles are important for gross motor functions. Impairment of these muscles can lead to poor postural control and ambulation difficulty. Little knowledge exists about the involvement of paraspinal muscles in Becker muscular dystrophy. Objective: In this cross-sectional study, we investigated the involvement of paraspinal muscles with quantitative trunk strength measure and quantitative muscle MRI. Methods and Materials: Eighteen patients with Becker muscular dystrophy underwent trunk, hip, and thigh strength assessment using a Biodex dynamometer and an MRI Dixon scan. Fourteen age- and body mass index-matched healthy men were included for comparison. Results: Muscle fat fraction (FF) of the paraspinal muscles (multifidus and erector spinae) was higher in participants with Becker muscular dystrophy vs. healthy controls at all three examined spinal levels (C6, Th12, and L4/L5) (p < 0.05). There was a strong and inverse correlation between paraspinal muscle FF and trunk extension strength (ρ = −0.829, p < 0.001), gluteus maximus FF and hip extension strength (ρ = −0.701, p = 0.005), FF of the knee extensor muscles (quadriceps and sartorius) and knee extension strength (ρ = −0.842, p < 0.001), and FF of the knee flexor muscles (hamstring muscles) and knee flexion strength (ρ = −0.864, p < 0.001). Fat fraction of the paraspinal muscles also correlated with muscle FF of the thigh muscles and lower leg muscles. Conclusion: In conclusion, patients with Becker muscular dystrophy demonstrate severe paraspinal muscular involvement indicated by low back extension strength and high levels of fat replacement, which parallel involvement of lower limb muscles. Assessment of paraspinal muscle strength and fat replacement may serve as a possible biomarker for both the clinical management and further study of the disease.